New Results for Homoclinic Fractional Hamiltonian Systems of Order α∈(1/2,1] - Abdelkader Moumen; Hamid Boulares; Jehad Alzabut; Fathi Khelifi; Moheddine Imsatfia (Fractal and Fractional, 2022)
In this manuscript, we are interested in studying the homoclinic solutions of fractional Hamiltonian system of the form <semantics>−<mmultiscripts>D∞ας</mmultiscripts>(<mmultiscripts>Dςα−∞</mmultiscripts>Z(ς))−A(ς)Z(ς)+∇ω(ς,Z(ς))=0,</semantics> where <semantics>α∈(12,1]</semantics>, <semantics>Z∈Hα(R,RN)</semantics> and <semantics>ω∈C1(R×RN,R)</semantics> are not periodic in <semantics>ς</semantics>. The characteristics of the critical point theory are used to illustrate the primary findings. Our results substantially improve and generalize the most recent results of the proposed system. We conclude our study by providing an example to highlight the significance of the theoretical results.